Coral Bleaching in the Persian/Arabian Gulf Is Modulated by Summer Winds - Paparella, Francesco; Xu, Chenhao; Vaughan, Grace O.; Burt, John A. (Frontiers in Marine Science, 2019)
Corals in the Persian/Arabian Gulf are the most thermally tolerant in the world, but live very near the thresholds of their thermal tolerance. Warming sea temperatures associated with climate change have resulted in numerous coral bleaching events regionally since the mid-1990s, but it has been unclear why unusually warm sea temperatures occur some years but not others. Using a combination of five years of observed sea-bottom temperatures at three reef sites and a meteorologically-linked hydrodynamic model that extends through the past decade, we show that summer sea-bottom temperatures are tightly linked to regional wind regimes, and that strong ‘shamal’ wind events control the occurrence and severity of bleaching. Sea bottom temperatures were primarily controlled by latent heat flux from wind-driven surface evaporation which exceeded 300 W/m^2 during shamal winds, double that of typical breeze conditions. Daily temperature change was highly correlated with wind speed, with breeze winds (<4 m/s) resulting in increased warming, while faster winds caused cooling, with the magnitude of temperature decline increasing with wind speed. Using observed and simulated data from 2012 to 2017, we show that years with reported bleaching events (2012, 2017) were characterized by low winds speeds that resulted in temperatures persisting above coral bleaching threshold temperatures for >5 weeks, while the cooler intervening years (2013-2016) had summers with more frequent and/or strong shamal events which repeatedly cooled temperatures below bleaching thresholds for days to weeks, providing corals temporary respite from thermal stress. Using observed data from 2012 onward and simulated data from 2008 - 2011, we show that the severity of bleaching events over the past decade was linked to both the number of cumulative days above bleaching thresholds (rather than total days, which obfuscates the cooling effects of occasional brief shamal events), as well as to maxima. We show that winds of 4 m/s represents a critical threshold for whether or not corals cross bleaching threshold temperatures, and provide simulations to forecast sea-bottom temperature change and recovery times under a range of wind conditions. The role that wind-driven cooling may play on coral reefs globally is discussed.